IT Industry as the Basis of Innovative Development Economy of Ukraine - Voloshinа, O.; Volodchenko, V.; Shashko, V. (Економічний вісник Донбасу, 2019)
The article defines basic information and communication resources and resources of national economy which allows to explain the phenomenon of informatization that appears as a social activity on the way of global community to the informative stage of development. Interprets the reasons for the contradiction between the significant innovational potential and low innovative development of economics of Ukraine. Positive and negative aspects of outsourcing are identified, the development direction of IT is explained. The ways to foster innovation in Ukraine are suggested. У статті визначено основні інформаційно-комунікаційні ресурси та резерви національної економіки, що дозволило обґрунтувати феномен інформатизації, який виступає у вигляді соціальної діяльності на шляху світового суспільства до інформаційної стадії розвитку. Розглянуто причини протиріччя між значним інноваційним потенціалом і низьким рівнем інноваційного розвитку економіки України. Визначено позитивні та негативні сторони аутсорсингу, обґрунтовано напрямок розвитку IT. Запропоновано шляхи для активізації інноваційної діяльності в Україні. В статье определены основные информационно-коммуникационные ресурсы и резервы национальной экономики, что позволило обосновать феномен информатизации, который выступает в виде социальной деятельности на пути мирового общества к информационной стадии развития. Рассмотрены причины противоречия между значительным инновационным потенциалом и низким уровнем инновационного развития экономики Украины. Определены положительные и отрицательные стороны аутсорсинга, обосновано направление развития IT. Предложены пути для активизации инновационной деятельности в Украине.